2015
DOI: 10.1590/0102-445039175922916369
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Integrated Teletandem: What have we been learning about writing and peer feedback?

Abstract: We defi ne institutionally integrated teletandem (iiTTD) as a series of teletandem sessions that are embedded in regular foreign

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…We understand that these fragments corroborate what other studies (BONFIM, 2014;BROCCO, 2014;CAVALARI, 2015;CAVALARI, 2016;LUVIZARI-MURAD, 2016) have shown -that iiTTD tasks may support foreign language learning and that peer feedback is highly valued by most participants. A key aspect of our analysis is the fact that the professor has a very important role to play as he/she puts the syllabus into practice by taking teletandem features into account.…”
Section: Fragment 15supporting
confidence: 89%
See 1 more Smart Citation
“…We understand that these fragments corroborate what other studies (BONFIM, 2014;BROCCO, 2014;CAVALARI, 2015;CAVALARI, 2016;LUVIZARI-MURAD, 2016) have shown -that iiTTD tasks may support foreign language learning and that peer feedback is highly valued by most participants. A key aspect of our analysis is the fact that the professor has a very important role to play as he/she puts the syllabus into practice by taking teletandem features into account.…”
Section: Fragment 15supporting
confidence: 89%
“…Within such a pedagogical setting, Bonfim (2014) investigated autonomy and showed that the integrating tasks may foster autonomous learning by offering support to students during the process. Brocco (2014) and Aranha and Cavalari (2015), who investigated asynchronous peer feedback offered by Brazilians to their partners' written productions in Portuguese, focused on the types of feedback and linguistic items addressed in text revision. Freschi (2017) studies the oral feedback offered during TOSs.…”
Section: Introductionmentioning
confidence: 99%
“…The teletandem activities in my study are defined as non-integrated (ARANHA; CAVALARI, 2015;LEONE;TELLES, 2016), which means that they were not bound to classroom contents or to a language syllabus. Bearing in mind that teletandem activities can also be institutionally integrated (ARANHA; CAVALARI, 2015; LEONE; TELLES, 2016), as they "are embedded in regular foreign language lessons" (ARANHA; CAVALARI, 2015, p. 763), future research could focus attention on the process of the co-construction of interculturality in the classroom by having participants reflect upon their online interactions.…”
Section: Final Remarksmentioning
confidence: 99%
“…The use of language (a key psychological tool) in social interactions is considered fundamental in learning, for it enables the emergence of what Vygotsky (1978, p. 86) called the zone of proximal development (ZDP) -" […] the distance between the actual developmental level as 1 See Cavalari and Aranha ([2016]) for a detailed characterization of this integrating task. See also Brocco (2014) and Aranha and Cavalari (2015) for a discussion on peer assessment practice in iiTTD.…”
Section: Collaborative Writingmentioning
confidence: 99%
“…Those theoretical tenets have oriented a pedagogical practice in the FL classroom that encourages learners to work in pairs (or groups) and to interact in the language they are learning. As to writing practice, group or pair work has been investigated by some researchers (LEE, 1997;FIGUEIREDO, 2005a;2005b;BITCHENER;YOUNG;CAMERON, 2005;CAVALARI, 2015) as peer feedback -a collaborative activity in which learners exchange writing drafts and offer feedback to help their fellow student improve their text. According to Storch (2013), in this kind of writing activity, collaboration is limited to the final phase of the writing practice (text revision) and the focus is on the product.…”
Section: Collaborative Writingmentioning
confidence: 99%